Are Shocks to Petroleum Products Consumption Permanent or Temporary: A New Evidence from LM Unit Root Tests with Structural Breaks - Sameh A. Ajlouni; Abdallah M. Ghazo; Ziad M. Abu-Lila (Emerging Science Journal, 2021)
The purpose of this paper is to examine whether shocks to the consumption of petroleum products in Jordan have permanent or temporary effects. This has been accomplished by applying Lee and Strazicich (2003) test of unit root with structural breaks to investigate the stationarity properties related to the time series of petroleum products consumption over the period 1961 to 2019. Empirical findings lend evidence that the consumption of petroleum products is a unit root process, implying that shocks to petroleum products consumption has permanent impact, and this consumption does not turn back to its time trend path following a shock. This indicates that there are high possibilities of energy demand management and conservation policies targeted towards achieving the intended goals in the long-run. In fact, this is compatible with the government energy strategies aimed at reducing the consumption of fossil oils. Doi: 10.28991/esj-2021-01279 Full Text: PDF